A Dialog Between Islamic Law and Adat (Customary Law) in the Social Context of West Kalimantan, Indonesia - Munawar, Munawar; Yusriadi, Yusriadi; Juniawati; Asfar, Dedy Ari; Tuah, Dilah (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the relationship between Islamic law (Sharia) and Customary law (Adat law) in the social context of West Kalimantan, Indonesia. The study's primary objective is to examine how these two legal systems coexist and interact within the region. The study employs a qualitative methodology, with data collection conducted through interviews with key informants, including religious leaders, Customary authorities, community members, and local government officials. The study also examines selected documents to ascertain the content of Customary law that is explicitly or implicitly related to Islamic law. The study finds that West Kalimantan Customary law has adopted Islamic law into its legal structure, as evidenced by the emergence of specific vocabulary or terms known in Islamic law that have similar meanings. Furthermore, there are differences in the situation between the Malay heartland, where Islam is strict, and the non-Malay heartland (Dayak Zone), where Islam is loose. These findings demonstrate local Customary law's active role, resilience, and adaptability in socio-economic change and broader legal reform. This study significantly contributes to law and sociology and offers a deeper understanding of the dialogue between Customary law and religion.